Proposta de protocolo para análise das encostas do rio Amazonas: um estudo de caso - OLIVEIRA, Maria Carolina Lira de (2023)
The “terras caídas” phenomenom is a type of landslide that happens mostly at riverside and riverbank areas of amazon rivers classified as “água branca”. The consequences of those landslides can be harmful and affecting the everyday lives of the locals. Considering the risk that this phenomenom can cause, its noticeable the necessity of investigation of its causes, and identification of the spots that the “terras caidas” is more likely to happen. The landslide case that happened in Santana/AP relates the phenomenom with the sensibility of the soil. This Project is a bibliographical research, with the main objective of propose a protocol for analisys of the Riverbanks Of Amazonas River and specifics objectives of identify the possible causes for this phenomenom; understand which tests are necessary to locate the risky areas; analyse the results of the piezocone test (CPTU), eletrorresistivity. The protocol proposed is composed of 3 stages: eletrorresistivity test; piezocone test (CPTU); and, ray-x diffractometry.